THE EFFECT OF KANGAROO CARE METHOD ON THE CHANGE OF BODY TEMPERATURE IN LOW BIRTH WEIGHT INFANTS (LBWI) - Bety Maya Sari; Dian Fitra Arismawati; Riska Aprilia wardani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
THE EFFECT OF KANGAROO CARE METHOD ON THE CHANGE OF BODY TEMPERATURE IN LOW BIRTH WEIGHT INFANTS (LBWI) Bety Maya Sari1, Dian Fitra Arismawati2, Riska Aprilia Wardani3 Correspondence email : Mayasari.bety@gmail.com Dian Husada Institute of Health Science Mojokerto ABSTRACT Introduction: Low Birth Weight Infants (LBWI) is infants with a birth weight of less than 2500 grams regardless of gestation. Babies with low birth weight (LBW) require proper care in order to avoid harmful things, one of which is Kangaroo Care Method. The purpose of this study is to determine the effect of kangaroo care method on changes in body temperature in LBW infants. Methods: The research design used was pre-experimental with design category (One group pretest-Post). Sampling technique used is consecutive sampling technique. Independent variable in this research is kangaroo care method. Variable dependent in this research is body temperature change. The data were collected through observation analysis with Wilcoxon test to determine whether there was any difference between two samples. The Results: The result of measuring body temperature in Low Birth Weight Infants indicates a change of given intervention kangaroo care method in body temperature with body temperature average of 36.30 C and there are 2 infants who had a decrease in body temperature after a given intervention. The result of statistic test showed that there was effect of kangaroo care method with Z value of 3.114 and with significant level of 0.002. Conclusion: The results of the research above proves that kangaroo care method can increase body temperature of in infants who experience LBW, so the kangaroo care method could be a substitute for incubator in overcoming hypothermia in LBW infants. Keywords: Kangaroo care method, body temperature, LBWI